2004
DOI: 10.1016/j.yexcr.2004.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids arrest breast cancer cell proliferation: retinoic acid selectively reduces the duration of receptor tyrosine kinase signaling

Abstract: Retinoic acid (RA) induces cell cycle arrest of hormone-dependent human breast cancer (HBC) cells. Previously, we demonstrated that RA-induced growth arrest of T-47D HBC cells required the activity of the RA-induced protein kinase, protein kinase Cα (PKCα) [J. Cell Physiol. 172 (1997) 306]. Here, we demonstrate that RA treatment of T-47D cells interfered with growth factor signaling to downstream, cytoplasmic and nuclear targets. RA treatment did not inhibit epidermal growth factor (EGF) receptor activation bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 79 publications
(103 reference statements)
2
8
0
Order By: Relevance
“…Early work has shown that cPKCs can themselves phosphorylate EGFR at Thr 654 , thereby decreasing the ligand affinity and signaling capacity of this receptor (63)(64)(65). Additionally, in a recent report, PKCa has been shown to phosphorylate protein tyrosine phosphatase PTP-1C, which in turn deactivates EGFR and decreases ERK phosphorylation in response to retinoid treatment in breast cancer cells (66). Taken together, these data support our notion that EGFR signaling is altered in the PKCa-deficient intestine.…”
Section: Crossbreedings Of Apcsupporting
confidence: 84%
“…Early work has shown that cPKCs can themselves phosphorylate EGFR at Thr 654 , thereby decreasing the ligand affinity and signaling capacity of this receptor (63)(64)(65). Additionally, in a recent report, PKCa has been shown to phosphorylate protein tyrosine phosphatase PTP-1C, which in turn deactivates EGFR and decreases ERK phosphorylation in response to retinoid treatment in breast cancer cells (66). Taken together, these data support our notion that EGFR signaling is altered in the PKCa-deficient intestine.…”
Section: Crossbreedings Of Apcsupporting
confidence: 84%
“…We and others have shown that ErbB and retinoid signaling systems interact with each other at multiple molecular and cellular levels (Grunt et al, 1998; Offterdinger et al, 1998, 1999, 2003; Schneider et al, 1999; Grunt, 2003; Tighe and Talmage, 2004). Preliminary data suggested that PD153035 elevates the expression of RAR‐β (Grunt et al, 2005).…”
Section: Resultsmentioning
confidence: 96%
“…We and others have previously shown that ErbB and retinoid pathways interact at several molecular and cellular levels with each other. For instance, retinoids downregulate the expression of ErbB receptors (Grunt et al, 1998; Offterdinger et al, 1998, 1999; Schneider et al, 1999) in breast and ovarian cancer and prematurely silence EGF signaling (Tighe and Talmage, 2004). Experimental evidence also indicates that heregulin—a ligand that binds ErbB‐3 or ‐4 and indirectly activates EGFR and ErbB‐2—cooperates with retinoids during stimulated in vitro differentiation of mammary carcinoma cells (Offterdinger et al, 2003).…”
mentioning
confidence: 99%
“…RA and its derivatives, collectively called retinoids, inhibit growth and induce apoptosis in a variety of epithelial cancer cells and hold great promise as chemotherapeutic agents [ 7 9 ]. Retinoids inhibit mitogen signalling [ 10 ] and induce downstream signalling pathways implicated in growth arrest, apoptosis and differentiation of precancerous and cancer cells [ 11 – 15 ]. However, with the exception of acute promyelocytic leukemia (APL) [ 14 , 16 , 17 ], clinical trials designed to test the efficacy of RA and its derivatives in the treatment of cancer have produced disappointing results, primarily because of RA-induced side effects and development of RA resistance [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%